SAT0226 A first-in-human, study of BMS-986165, a selective, potent, allosteric small molecule inhibitor of tyrosine kinase 2. (15th June 2017) - Catlett, I; Aras, U; Liu, Y; Bei, D; Girgis, I; Murthy, B; Honczarenko, M; Rose, S
Abstract : Background: Tyrosine kinase 2 (Tyk2) is a member of the JAK family that phosphorylates STAT proteins downstream of the IL-12, IL-23 and the Type I interferon receptor. Tyk2 genetic variants have been linked to multiple autoimmune diseases, 1 with a deactivating coding variant conferring significant protection against multiple immune-mediated disorders including systemic lupus erythematosus (SLE). 2 Selective pharmacologic inhibition of Tyk2 has proven daunting, given the high degree of similarity among JAK catalytic domains. Using a novel approach, we have developed BMS-986165, a highly selective and potent small molecule inhibitor, which blocks receptor-mediated Tyk2 activation by stabilizing the regulatory pseudokinase domain of the protein. Lupus-like disease is strongly inhibited in NZB/W mice treated with BMS-986165. Together, these data establish Tyk2 as a highly promising therapeutic target for SLE. Objectives: We report the first evidence of safety, pharmacokinetics (PK), target engagement (TE), and pharmacodynamic activity (PD) of BMS-986165, a novel inhibitor of Tyk2. Methods: Safety, PK, TE, and PD were assessed in a randomized, double-blind, single and multiple ascending dose study of 108 (83 active: 25 placebo) healthy participants (NCT02534636 ). Target engagement was assessed by an ex vivo assay, IL-12 and IL-18 induced IFNγ production. Roferon-A was administered to assess in vivo pharmacodynamic effects of BMS-986165 on physiological manifestations of IFN exposure and on IFN-regulated gene (IRG) expression. Results: BMS-986165 was safe and overall well-tolerated. There were no serious adverse events and the frequency of non-serious adverse events were similar in the active (75%) and placebo (76%) groups. The most frequently reported adverse events by preferred term were headache (23% active versus 28% placebo), nausea (12% active versus 8% placebo), rash (12% active versus 8% placebo), and upper respiratory tract infection (11% active versus 12% placebo). After oral administration, BMS-986165 was rapidly absorbed and exhibited an apparent elimination half-life of 8–15 hours. Modest accumulation (1.4x-1.9x) was observed after multiple dosing. BMS-986165 inhibited IL-12/IL-18-induced IFNγ production in ex vivo assays in a dose and concentration dependent manner. Following an in vivo challenge with a clinical dose of Interferon-alfa-2A, BMS-986165 demonstrated dose-dependent inhibition of lymphocyte count decreases and expression of 53 IRGs in blood (Figure 1 ). Conclusions: BMS-986165 is a safe and potent Tyk2 inhibitor with clear evidence of ex vivo and in vivo biologic activity in healthy participants, and the potential for once daily dosing. Overall, Inhibition of IL-12/23 and type I IFN pathways support further testing of BMS-986165 in diseases such as lupus and psoriasis. A Phase 2 study in patients with moderate-to-severe psoriasis is ongoing (NCT02931838 ). References: Liang Y, Zhu Y, Xia Y, Peng H, Yang XK, et al. Therapeutic potential of tyrosine kinase 2 in autoimmunity. Expert Opin Ther Targets. 2014 May;18(5):571–80. Dendrou CA, Cortes A, Shipman L, Evans HG, Attfield KE, et al. Resolving TYK2 locus genotype-to-phenotype differences in autoimmunity. Sci Transl Med. 2016 Nov 2;8(363):363ra149. Disclosure of Interest: I. Catlett Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, U. Aras Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, Y. Liu Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, D. Bei Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, I. Girgis Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, B. Murthy Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, M. Honczarenko Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, S. Rose Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb